Two new acylated flavonol glycosides from Mimosa pigra L. leaves sub-family Mimosoideae - Chinedu J. Okonkwo; Obioma U. Njoku; Tochukwu J.N. Okonkwo; Ozadheoghene E. Afieroho; Peter Proksch (SpringerOpen, 2016)
Background: Mimosa pigra L. (Fabaceae-Mimosoideae) is a large shrub native to tropical America and economically important as a medicinal plant; it is also an invasive plant and a noxious weed. Methods: M. pigra leaves were air dried, pulverised and extracted with 96% ethanol. The ethanol extract (MPEE) was partitioned with diethyl ether (DEE) and ethyl acetate (EA) in succession to yield DEE fraction (DEEF), EA fraction (EAF) and EA insoluble fraction (EAIF). Results: Sephadex LH-20 gel filtration chromatography (GFC) of the EAF and semi-preparative HPLC purification of the GFC sub-fractions afforded two new acylated flavonol glycosides [myricetin (2"-O-galloyl)-3-O-α-l-rhamnopyranoside, I; and quercetin (2"-O-galloyl)-3-O-α-l-rhamnopyranoside, II] in M. pigra. Alongside three other flavonol glycosides (myricetin 3-O-α-l-rhamnopyranoside, III; quercetin 3-O-α-l-rhamnopyranoside, IV; and quercetin 3-O-α-l-arabinopyranoside, V). The structures of compounds I-V were assigned by ultraviolet/visible (UV) spectroscopy, 1D and 2D 1H and 13C NMR spectroscopy and liquid chromatography-electrospray-mass spectrometry (LC-ESI-MS). Conclusion: Myricetin, quercetin and their glycoside derivatives are strong antioxidants; and elicit cytotoxic effect on human cancer cell lines among other pharmacological activities. The isolation of acylated flavonoids in M. pigra provided an important insight on the evolutionary trend of the medicinal plant. While the dominance of flavonols, may account for the various ethnomedicinal uses of the herb and the mechanism and mode of its confirmed pharmacological actions.